NETWORKED VOICES, DIGITAL SOLIDARITY: FEMINIST RESISTANCE AND MEDIA MOBILIZATION IN CONTEMPORARY ALGERIA - Bouaziz, Amina; Hamzaoui, Ahlem (Armenian Folia Anglistika, 2025)
This study looks at how feminist activism in contemporary Algeria has been transformed by digital and independent audio media, such as podcasts and radio. Feminists have used these platforms to document their fight for gender justice, build solidarity across various societal segments, and get around state-controlled narratives while operating under a repressive government and patriarchal laws like the 1984 Family Code. According to the study, these media create a decentralized feminist network that cuts across regional, linguistic, and class barriers in Algeria. It examines important activists and media initiatives while recognizing persistent issues like societal norms, the digital divide, and state surveillance. The study illustrates how the media has significantly raised Algerian women’s visibility and power through qualitative analysis and case studies from the Hirak protests (2019–2025). The study’s final conclusion is that media are essential venues for activism and active participants in determining the future of women’s rights and democracy in Algeria, rather than just being tools for communication.